The dismission from the positive legal responsibility and the principle of inevitable: the aspects of correlation - Корнієнко, Андрій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article we investigate the aspects of correlation between the dismission from the positive legal responsibility and the principle of inevitable